“Biosimilar” generic version of biologic products? - M Taher; Siti Syazwani Shaari; Deny Susanti (Institut Teknologi Bandung, 2021)
Biosimilars are currently popular after the expiry date of patents for biological reference products have expired or soon will expire. Besides, this ‘copycat’ version of biologic products offers much lower costs as compared to the reference products, thus promoting better patient access to the treatment of certain diseases such as cancer, inflammatory diseases, skin disorders, and diabetes. This review aims to determine the differences between biosimilars and generic drugs and highlight some issues related to biosimilar products such as comparability, interchangeability, immunogenicity, extrapolation of indication, current legislation, pharmacovigilance, and naming system. Scientific sources from PubMed, Google Scholar, ScienceDirect, and Elsevier were accessed for preparation of this review article. Biosimilars are not generic drugs as they have a larger and complex structure as compared to generic drugs. Due to that, biosimilars are highly similar but not identical to the reference products. Many regulatory authorities have authorized biosimilars under a distinct regulatory process from that of the generic drugs and subjected them to comprehensive comparability studies with their reference products (analytical, nonclinical in vitro, in vivo studies, and clinical trials). Additional evidence from interchangeability studies, extrapolation of indication studies, immunogenicity profile assessments, and pharmacovigilance studies are also beneficial to assess the efficacy, safety, and quality of the biosimilar before and/or after receiving their regulatory approval. Biosimilars are different from generic drugs due to their complexity in structure and manufacturing process. More comprehensive studies are required to ensure their benefits outweigh the risks.